The Potential of Saponin in Sea Cucumbers to Prevent Hyperlipidemia - Talitha Syahla; Diki Wahyudi; Sima Smith; Yumna Iftinan Khalda; Zulfa Hasyimiyyah Ihtisyam; Dini Suryani (Jurnal Biologi Tropis, 2023)
Hyperlipidemia is the main risk factor for atherosclerosis which can cause death. The occurrence of hyperlipidemia is relatively high with a percentage of 45% globally and 35% in Indonesia.  The purpose of this article is to determine the potential of saponins in sea cucumbers as the ingredients used to prevent hyperlipidemia. The method used in this article is a literature study by collecting relevant and focused articles. The literature used were the National Center for Biotechnology Information (NCBI), the Multidisciplinary Digital Publishing Institute (MDPI), and Google Scholar. The results of the literature review carried out are that the saponins found in sea cucumbers are the main component as a lipid reducer compared to other compounds found in sea cucumbers. In conclusion, saponins in sea cucumbers influence lipid metabolism which ultimately prevents hyperlipidemia through various mechanisms.